THE EFFECT OF KNOWLEDGE MANAGEMENT AND THE ROLE OF HUMAN RESOURCES FOR STRATEGIC PLANNING AND ORGANIZATIONAL PERFORMANCE: A STUDY AT HOSPITALS OF NORTH SULAWESI, INDONESIA - Armanu; Noermijati; Sudiro A.; Moningkey G. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
The aim of this study is to determine, and evaluate the influence of the knowledge management and the role of human resources as a strategic partner in the strategic planning and organizational performance. The study conducted in public hospitals and the private sectors in the region of Nort Sulawesi with the respondent is the head of the hospital in upper and middle levels. At each hospital is given three respondents representing organizations and the unit of analysis is the organization. The data collected directly from respondents using research instruments. Techniques of analysis used partial least square (PLS). The result proves the knowledge management and the role of human resources as a strategic partner to improve the accuracy of strategic planning, and strategic planning can improve organizational performance. Knowledge management is also shown to increase the role of human resources as strategic partner. Knowledge management does not directly affect the performance of organization, but it proved that the strategic planning mediate the influence of knowledge management on organizational performance. This suggests that knowledge management is not a direct determinant of organizational performance, but its existence becomes an important input of the strategic planning process in an effort to improve organizational performance. The role of human resources as a strategic partner also not directly affects the performance of organization, and strategic planning proved to mediate the role of perfect pair strategic human resources relationship with organizational performance. This illustrates that the involvement of human resources executive as a strategic partner is not direct determinant of organizational performance, but the strategic role of a source of organizational capabilities to conduct strategic planning, in an effort to improve organizational performance. Based on these results, it means that strategic planning is based on the knowledge management and human resources role as a strategic partner can be a strategic capabilities, are valuable, rare, inimitable and non substitutable. These capabilities can become the core competencies of the organizations to improve or enhance the performance, which is a source of competitive advantage of the organization in a changing business environment rapidly.